Hóros and asápheia in Aristotle. Are metaphors obscure? - Zagal Arreguín, Héctor (Estudios de Filosofía, 2001)
Aristotle is recognized in the history as thefather of logic. The article highlights two points. First, it analyzes the reasons why Aristotle rejects frequently the metaphorical definition, specially, in the scope of the so called metaphysics. Secondly, it brings forth some methodological inconsistencies in the Corpus about it.